Empowering youth & transforming communities through job creation & nutritious beans in Kenya - Ong'or, Dennis; Inyanji, Eileen; Rubyogo, Jean Claude; Waswa, Boaz; Mabeya, Justin; Mwiti, Emily; Maritim, Mary; Karanja, David (2025)
In Kenya, the dependency on bean imports and the underutilization of domestic production opportunities has led to significant economic and employment gaps in the country’s agricultural sector. Addressing this challenge, the project “Nutritious Bean Products for Decent Employment for Youth in Kenya (NBP-DEYK),” initiated in 2021 by the Alliance of Bioversity International and CIAT in collaboration with the Kenya Agricultural and Livestock Research Organization (KALRO) and other partners, sought to empower youth, especially young women, through the production and processing of high iron and zinc beans (HIB). The project aimed to create at least 500 job opportunities—120 newly created jobs and 380 improved jobs—by leveraging the potential of HIB in the bean value chain. By the end of 2024, Cherubet Foods alone had created 110 new jobs, with 92% of these positions filled by youth, and improved over 500 existing roles, benefiting farmers, processors, and traders. The project also fostered growth within local farmer cooperatives, with a notable increase in women’s participation. Gender and age disaggregation showed that 60% of the new jobs went to young women, and 29% to young men. With these successes, the project demonstrates the potential for youth and women empowerment through agriculture, sustainable job creation, and community resilience. The results underscore the importance of leveraging partnerships, innovation, and technology to scale and sustain youth empowerment and community development efforts in Kenya.